2023
DOI: 10.1136/bmjopen-2022-069281
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal multimorbidity and preterm birth, low birth weight and small for gestational age: a prospective birth cohort study from the Japan Environment and Children’s Study

Abstract: ObjectivesMultimorbidity is defined as the coexistence of two or more chronic physical or psychological conditions within an individual. The association between maternal multimorbidity and adverse perinatal outcomes such as preterm delivery and low birth weight has not been well studied. Therefore, this study aimed to investigate this association.MethodsWe conducted a prospective cohort study using data from the Japan Environment and Children’s Study of pregnant women between 2011 and 2014. Those with data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, several recent studies have reported an increased risk of extreme PTB (<28 weeks) among women with obesity (BMI ≥ 30 kg/m 2 ) [37][38][39][40][41]. Furthermore, previous studies involving women of diverse ethnicities have indicated an association between obesity and extreme PTB [42][43][44]. Shaw et al conducted a comprehensive analysis of the link between prepregnancy BMI and sPTB in a large population-based cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several recent studies have reported an increased risk of extreme PTB (<28 weeks) among women with obesity (BMI ≥ 30 kg/m 2 ) [37][38][39][40][41]. Furthermore, previous studies involving women of diverse ethnicities have indicated an association between obesity and extreme PTB [42][43][44]. Shaw et al conducted a comprehensive analysis of the link between prepregnancy BMI and sPTB in a large population-based cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Naksini K et al published the first paper investigating the association between maternal multimorbidity and perinatal outcomes [ 10 ]. Their study reported a lower prevalence of multimorbidity (6.3%) compared to ours and to previous studies [ 4 , 28 ], which can be attributed to differences in the definition of multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of multimorbidity on maternal and pregnancy outcomes is poorly understood as most research has focused on individual maternal diseases to date. There is limited knowledge on the prevalence [ 5 , 6 ], causes and consequences of multimorbidity during pregnancy on maternal and birth, and neonatal outcomes [ 7 10 ]. One recent paper has reported an association between maternal multimorbidity and preterm birth (PTB) and other adverse perinatal outcomes [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a cross-sectional study among the UK population estimated that the prevalence of coexisting multiple chronic conditions ranged from 19.8% to 46.2% in pregnant women and was associated with higher odds of preterm birth (adjusted odds ratio (aOR) = 1.64; 95% confidence interval (CI) = 1.48–1.82) [ 13 , 14 ]. Similarly, maternal multimorbidity was found to associate with preterm birth, low birthweight, and small for gestational age according to a study conducted in Japan [ 16 ]. Another study from India expanded the spectrum of MHFP by including maternal risks, lifestyle risks, medical risks, current health risks, and previous birth outcome risks, and found that 16.4% of the women in the study population had two or more high-risk factors simultaneously [ 18 ].…”
mentioning
confidence: 99%